2004
DOI: 10.1080/01443610310001620369
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin fluorescence characteristics and standard semen analysis parameters: correlations observed in andrology testing among 136 males referred for infertility evaluation

Abstract: This paper aims to describe the relation between standard semen analysis parameters (concentration, motility and morphology) and sperm chromatin structure assay (SCSA) results among patients referred for infertility evaluation. Healthy males (n=136) seeking infertility consultation were evaluated prospectively by semen analysis and sperm chromatin structure assay (SCSA). Significant inverse correlations were observed between high sperm concentration and DNA fragmentation index (DFI) and high DNA stainability (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 9 publications
7
23
0
1
Order By: Relevance
“…Zini et al [39] demonstrated negative correlations between sperm DNA integrity and sperm quality in partners of couples attending IVF clinics. Additionally, in a small cohort of patients consulting for infertility investigation, prospective analyzes showed that both sperm motility and sperm morphology were inversely correlated to the rate of nuclear DNA fragmentation [10][11][12]36]. These results corroborated with our findings and suggested that sperm motility and morphology defects may be in part due to a reduction of sperm DNA integrity which can be promutagenic and can adversely affect fetal outcome after IVF and has lifelong implications on health of child [34].…”
Section: Discussionsupporting
confidence: 88%
“…Zini et al [39] demonstrated negative correlations between sperm DNA integrity and sperm quality in partners of couples attending IVF clinics. Additionally, in a small cohort of patients consulting for infertility investigation, prospective analyzes showed that both sperm motility and sperm morphology were inversely correlated to the rate of nuclear DNA fragmentation [10][11][12]36]. These results corroborated with our findings and suggested that sperm motility and morphology defects may be in part due to a reduction of sperm DNA integrity which can be promutagenic and can adversely affect fetal outcome after IVF and has lifelong implications on health of child [34].…”
Section: Discussionsupporting
confidence: 88%
“…2). This correlation confirms the findings of previous studies (47,48), whereas other studies found weaker or no associations (25,27,39). The finding that DFI and motility were both strongly associated with age and duration of abstinence suggests that a common mechanism related to oxidative stress may be responsible.…”
Section: Discussionsupporting
confidence: 81%
“…Since 1980, U.S. birth rates have increased up to 40% for men [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] years and have decreased up to 20% for men under 30 (1). Although it is well known that as women age, they are at increased risk for infertility, spontaneous abortion, and genetic and chromosomal defects among offspring, the association of male aging with these outcomes has been less well characterized (2).…”
mentioning
confidence: 99%
“…Negative correlations with the percentage of normal sperm morphology have also been found [Irvine et al 2000;Lopes et al 1998;Sills et al 2003;Brahem et al 2011]. The correlation most frequently reported for DNA fragmentation is a high negative relationship with sperm motility [Lopes et al 1998;Sills et al 2003;Giwercman et al 2003], as shown in our study.…”
Section: Discussionsupporting
confidence: 73%